Effects of oral anorexiant sibutramine on the expression of cytochromes P450s in human hepatocytes and cancer cell lines - Vrzal, Radim; Knoppová, Barbora; Bachleda, Petr; Dvořák, Zdeněk (Journal of biochemical and molecular toxicology, 2013)
Sibutramine is a serotonin-norepinephrine reuptake inhibitor that was used for weight-loss management in obese patients. Even though it was officially withdrawn from the market in 2010, it is still present in some tainted weight-loss pills (as reported by US Food and Drug Administration). Thus, it is still reasonable to study the effects of this compound. The aim of this work was to investigate the potential of sibutramine to induce CYP1A1/CY3A4 in human cancer cell lines and CYP1A1/2, CYP2A6, CYP2B6, and CYP3A4 in human hepatocytes, a competent model of metabolically active cells. The levels of mRNA and protein of CYP1A1/1A2/3A4/2A6/2B6 were compared with the typical inducers, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and rifampicin (RIF) for CYP1A1/2 and for other CYPs, respectively. The mRNA and protein levels of all genes in either cancer cell lines or human hepatocytes were induced when treated with typical inducers but not with sibutramine.
Keywords: RNA, Messenger; látky proti obezitě; Isoenzymes; Primary Cell Culture; Cell Line, Tumor; kvantitativní polymerázová řetězová reakce; izoenzymy; Hepatocytes; Humans; Cyclobutanes; Real-Time Polymerase Chain Reaction; western blotting; primární buněčná kultura; cyklobutany; Cytochrome P-450 Enzyme System; hepatocyty; Anti-Obesity Agents; systém (enzymů) cytochromů P-450; messenger RNA; nádorové buněčné linie; Blotting, Western; lidé